Patterns of skin substitute use in isolated face and hand burns - Rachel M. Nygaard; Frederick W. Endorf (Elsevier, 2017)
Non-medical factors may influence a wide variety of medical care. This study uses a large national database to examine potential factors influencing the use of skin substitutes in patients with face and hand burns. A total of 2847 patients with isolated 3rd degree hand and face burns from the NBR were identified from the NBR. Of those 2847 patients, 2299 (81%) had autografting alone. 143 patients (5%) had heterografting followed by autografting, 318 (11%) had homografting followed by autografting, and 87 patients (3%) had a dermal regenerative graft followed by autografting. Findings indicated that race and insurance status may influence the use of skin substitutes in isolated face and hand burns. Dermal regenerative grafts are more likely to be used in white patients with commercial insurance (p < 0.001), whereas homografting is more likely to be used in non-white patients with commercial insurance (P < 0.001). Potential factors contributing to these findings are not all available in this large national database, but awareness of these trends is important when deciding on an operative plan in patients with face and hand burns. Keywords: Skin substitutes, Burns, Face, Hands